Relationship between strength and muscle mass in middle-aged and elderly women: a cross-sectional study - Souza,Carine Fernandes de (2017)
Abstract Objective: to analyze the relationship between handgrip strength and lower limb strength and the amount of segmental skeletal muscle mass in middle-aged and elderly women. Methods: an observational, cross-sectional, observational study of 540 women aged between 40 and 80 years in the cities of Parnamirim and Santa Cruz, Rio Grande do Norte, was performed. Sociodemographic data, anthropometric measurements, handgrip dynamometry, knee flexors and extensors of the dominant limbs, as well as the segmental muscle mass of the limbs were evaluated. Data were analyzed using Student's t-Test, Chi-square test, Effect Size and Pearson's Correlation (CI 95%). Results: there were statistically significant weak and moderate correlations between handgrip strength and upper limb muscle mass, knee flexion strength and lower limb muscle mass, and between knee extension strength and lower limb muscle mass for the age groups 40-59 years and 60 years or more (p<0.05). Conclusions: muscle strength correlates with skeletal muscle mass. It could therefore be an indicator of the decrease in strength. It is not the only such indicator, however, as correlations were weak and moderate, which suggests the need for more studies on this theme to elucidate which components may also influence the loss of strength with aging.